FACTORS INFLUENCING THE ADOPTION OF DIGITAL TECHNOLOGIES BY SMALL-SCALE PRODUCERS IN INDIA'S AGRICULTURE VALUE CHAINS (AVCS) - Sahil, Dr. Vinod Kumar Bishnoi (Chelonian Research Foundation, 2022)
Digital technology presents significant opportunities for small-scale farmers in tackling the diverse difficulties encountered within Agriculture Value Chains (AVCs). Nevertheless, small-scale farmers encounter considerable obstacles that impede their adoption of digital technologies. This research investigates the various economic, social, and political factors that impact the adoption and deployment of digital solutions in autonomous vehicle companies (AVCs). This study provides significant insights into the governance implications and institutional barriers related to the investigation of digital technology adoption. In order to obtain empirical data, the study utilised a rigorous approach, acquiring information from a sample of 480 farmers located in the state of Haryana, India. The attainment of this objective was facilitated by the implementation of structured questionnaires and the use of the snowball sampling methodology, thereby guaranteeing the acquisition of a dataset that is representative of the population under study. The results of the regression study highlight the primary influence of economic factors on the adoption of digital agriculture solutions, with social and political aspects closely following suit. This highlights the necessity of a developmental framework that is tailored to the individual situation, in order to facilitate the successful incorporation of digital solutions within the small-scale farming sector. The findings underscore a positive pattern, whereby farmers are increasingly adopting digital tools to improve their agricultural methods. The primary driving force behind this phenomenon is mostly attributed to the appeal of financial advantages and the existence of favourable governmental policies. This study contributes a crucial dimension to our comprehension of the dynamics related to the adoption of digital technology in the agricultural sector. It elucidates the complex interaction among economic, political, and social factors, and presents a potential trajectory for the progress of small-scale farmers in the era of digitalization. KEYWORDS: Digital Technology, Agriculture Value Chains, Economic Factors, Social and Political